EP389 Does laparoscopic extra-peritoneal para-aortic node dissection aid treatment of women with locally advanced cervical carcinoma? A 9 year review of one institution in northern ireland. (1st November 2019) - Reilly, K; Craig, E; Dobbs, S; McComiskey, M; Nagar, H; Harley, I
Abstract : Introduction/Background: Cervical cancer is one of the most commonly occurring female cancers with increasing incidence worldwide. The mainstay of treatment for locally advanced cervical cancer is primary chemoradiotherapy. Pre-operative imaging alongside laparoscopic extraperitoneal para-aortic node dissection (LEPAND) has been used in order to best target this treatment. This study looked at all the women in the Belfast Trust over the last 9 years who had this investigation done as part of their pre-treatment workup and their outcomes. Methodology: Retrospective data was collected for all those who had LEPAND for locally advanced cervical cancer from January 2010 to December 2018. These women all had pre-operative imaging that suggested positive pelvic lymph nodes but negative para-aortic nodes therefore deeming them suitable for the surgery. Results: Sixty women were identified in this group with an age range from 23–69 and median age of 39. 93.3% had stage 2b cervical cancer, the remainder were 1b2 or 3b. 17% had adenocarcinoma of the cervix and 83% had squamous cell carcinoma. 70% of the women had primary LEPAND surgery before chemoradiotherapy with the remainder having their primary treatment before surgery. 5% (3/60) had positive para-aortic nodes on histopathology although 100% appeared node negative on MRI or PET imaging. None of those with positive nodes had recurrences but 66% died within 2 years. 15% of the study population died with 90% of these in the two years after diagnosis. 67% of these women had primary LEPAND followed by chemoradiotherapy with the others proceeding straight to primary treatment. The median survival for this group is 5 years. Conclusion: 5% of the group had positive para-aortic lymph nodes on histopathological examination. This was despite imaging stating that they were node negative.LEPAND surgery prevented undertreatment in these women by re-targeting their radiotherapy. Disclosure: Nothing to disclose.